Vývoj znalostí o idiopatických střevních zánětech - Hrabák, Petr; Hrabák, Pavel; Štajnerova, Markéta; Novotný, Aleš; Lukáš, Karel (Casopis lekaru ceskych, 2016)
Crohns disease and ulcerative colitis has affected people for many centuries however its incidence most likely used to be very low. The knowledge of the idiopathic intestinal inflammation at that time was also very limited - an interest about the disease has emerged since the second half of 19th century. Despite all the progress in medicine its etiology still remains unclear.Diagnosis had for a long been based only on clinical investigation and later radiography, endoscopy came in to use in the 1970s. First significant advances in therapy came during the 1940s and 1950s with the invention of aminosalicylates, antibiotics and corticoids. The most advanced conservative therapy today is biological treatment although the importance of gastrointestinal surgery should not be overlooked.The aim of this article is to briefly review the development of knowledge of the idiopathic intestinal inflammation with an emphasis on the 20th century.
Keywords: Crohns disease.; idiopatické střevní záněty; Endoscopy, Gastrointestinal; ulcerative colitis; gastrointestinální endoskopie; lidé; Inflammatory Bowel Diseases; Humans; Aminosalicylic Acid; kyselina aminosalicylová; inflammatory bowel diseases